Solving Food Security Problems Through Ideas, Creativity, Innovation and Commercialization (ICIC) Ways in Tropical Animal Production Systems - Dahlan, Ismail (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
This paper attempts to apply system thinking in solving food security problems especially intropical countries. System thinking is synonymous with ICIC ways which means Idea, Creativity,Innovation, and Commercialization. Through ICIC ways agriculture production systems can beefficiently managed and sustainable. In order to solve food security problems we need to consider3Ps (people, planet and profit) aspect of development. Three examples will be used to explain ICICapproach are livestock-crop plantation (LICRO) integrated production systems as a future animalproduction system in the tropics, oil palm fronds (OPF) as a fiber source for herbivores feeding anddehydrated-processed food waste (DFW) as an ingredient in poultry feed formulation for free rangesystem. This paper will apply system approach to solve some of livestock production problems suchas limited grazing land space for ruminant (cattle, buffalo, goat, sheep and deer), utilizing readilyavailable green fiber source (waste) such as OPF as herbivore feedstuff and re-utilize food waste(processed and dehydrated) from restaurants, hospital canteens, hotels and others as replacementfor expensive imported feed grains in poultry feeding management. Food security problems in termof low in self-sufficiency level in animal protein food such as meat and milk from ruminants and egg&poultry meat can be solved efficiently and economically through application of appropriatetechnology and innovations. All problems can be turned into opportunities through ICIC ways; notonly solving primary problem of resource scarcity but also contributes towards multiple output andcommercialization of animal protein food items and animal products from the system.Key Words: Â Food Security, System Thinking, Idea, Creativity, Innovation, Commercialization, Â Â Integrated Livestock-Crop Plantation System, Oil Palm Frond Fiber Feed, Food Wasteas Feed